The impact of profit taxation on capitalized investment with options to delay and divest - Georg Schneider; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2010)
In entrepreneurial decisions making uncertain future profits often are a main characteristics of real investment opportunities. If investors can react to uncertainty the degree of irreversibility and timing flexibility inherent in the available project should be integrated into the decision calculus. In this paper we investigate the interdependencies of effects from profit taxation and real options. We model an investment decision including an option to invest and an option to abandon. We show that increasing the tax rate can lead to paradoxical tax effects, i.e. may foster an investor's willingness to invest into a capitalized investment. Instead, if we abstract from the possibility to abandon the investment object such paradoxical effect cannot be identified. Determining the after-tax value of the option to enter the investment project with and without an abandonment option we receive a critical cash flow cutoff level. We find that the value of the option to abandon depends on the tax rate and the amount of periodical cash flows. The option value can be increasing or decreasing in the tax rate. We find scenarios with paradoxical tax effects and show that the observed paradoxical effects are due to the presence of the real abandonment option itself. This finding contributes to the stream of literature that explains potential sources of paradoxical tax effects. The generated decision rules are helpful for investors facing risky investment opportunities and for discussing the economic impact of tax reforms. Furthermore, we highlight the overwhelming importance of integrating taxes in typically applied valuation approaches.
Keywords: H25; H21; 330; investment decisions; real options; tax effects; timing flexibility; uncertainty; Ertragsteuer; Steuerwirkung; Betriebliche Investitionspolitik; Realoption; Zeit; Theorie